Medication-related burden and its association with medication adherence among elderly tuberculosis patients in Guizhou, China: a cross-sectional study - Wang, Yun; Jian, Sisi; Huang, Zhongfeng; Chen, Huijuan; Hu, Yuanxia; Fang, Shilin (Frontiers in Pharmacology, 2024)
Tuberculosis (TB) morbidity and mortality are significantly increasing in the elderly worldwide. Their optimal health outcomes are hampered by medication-related burden (MRB) and poor treatment adherence. Understanding the MRB status from patients’ perspectives and its association with adherence among elderly TB patients will help achieve the End TB targets. Thus, we aimed to identify the incidence of MRB and nonadherence among elderly TB patients in Guizhou, and determine their association. A cross-sectional study was conducted in three prefectures with high TB notifications in Guizhou in 2022. The data were collected via face-to-face structured interviews. MRB was measured using the Living with Medicines Questionnaire version 3 (LMQ-3), which consists of eight domains. Nonadherence was assessed by treatment interruption, which was defined as any interruption lasting at least one day at any time within the last three months. A binary unconditional logistic regression model was used to determine the association between variables. Of the 405 elderly TB patients enrolled, 49.4% and 42.7% of the respondents perceived suffering from moderate and high MRB, respectively. The incidence of nonadherence among patients was 33.6%. Patients with higher scores in domain 2 (practical difficulties) [ORadj = 1.19; 95% CI (1.11-1.28)] and domain 4 (side effects burden of prescribed medications) [ORadj = 1.16; 95% CI (1.06-1.27)] were more likely to experience nonadherence. But, patients with higher scores in domain 8 (control/autonomy of medicine use) [ORadj = 0.70; 95% CI (0.61, 0.81)] were more likely to occur adherence. Patients with a high education level [ORadj = 0.29; 95% CI (0.08, 0.92)] had a decreased risk of nonadherence, but those with a living expense from a retirement salary [ORadj = 2.55; 95% CI (1.16, 5.71)] had an increased risk of nonadherence. The incidence of MRB and medication nonadherence is high among elderly TB patients in Guizhou. The significant associations between the three domains of MRB and nonadherence highlight that measuring MRB in multiple dimensions using the LMQ-3 in elderly TB patients could assist clinicians in providing patient-centered care, and multifaceted interventions targeting the identified problems should be implemented to reduce MRB and nonadherence among elderly TB patients in Guizhou.